2013
DOI: 10.1371/journal.pone.0074645
|View full text |Cite
|
Sign up to set email alerts
|

Low Control over Palatable Food Intake in Rats Is Associated with Habitual Behavior and Relapse Vulnerability: Individual Differences

Abstract: The worldwide obesity epidemic poses an enormous and growing threat to public health. However, the neurobehavioral mechanisms of overeating and obesity are incompletely understood. It has been proposed that addiction-like processes may underlie certain forms of obesity, in particular those associated with binge eating disorder. To investigate the role of addiction-like processes in obesity, we adapted a model of cocaine addiction-like behavior in rats responding for highly palatable food. Here, we tested wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…Although this model had previously been employed to study motivation for cocaine-seeking, the authors reported that even mild foot-shocks suppressed all food-seeking by the rats. De Jong et al (2013) then switched to quinine adulteration of the palatable food as an alternative to evaluate punished responding in the rats. They observed that quinine adulteration suppressed operant responding for food to the same extent in the binge-eating and control groups of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Although this model had previously been employed to study motivation for cocaine-seeking, the authors reported that even mild foot-shocks suppressed all food-seeking by the rats. De Jong et al (2013) then switched to quinine adulteration of the palatable food as an alternative to evaluate punished responding in the rats. They observed that quinine adulteration suppressed operant responding for food to the same extent in the binge-eating and control groups of rats.…”
Section: Discussionmentioning
confidence: 99%
“…This sensitized response is indicative of enhanced responsivity of mesolimbic systems and is consistent with studies in humans suggesting that pre-existing differences in striatal motivational systems may contribute to obesity and hamper weight loss (Stice and Dagher, 2010, Berthoud et al, 2011, Volkow et al, 2011, Demos et al, 2012, Murdaugh et al, 2012). We speculate that pre-existing hyper-sensitivity of mesolimbic systems may facilitate neuroadaptations induced by eating sugary, fatty foods, and thereby further enhance responsivity to food cues in susceptible individuals (Robinson et al, 2015) and hamper the control of food intake (Wang et al, 2002, Johnson and Kenny, 2010, de Jong et al, 2013). Further studies using models that differentiate pre-existing from diet and/or obesity induced plasticity in motivational systems will continue to add to our understanding of how interactions between these factors contribute to the development and persistence of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after an extended history of cocaine self-administration, rats will continue to press a lever to obtain a cocaine infusion when a tone is presented that is previously associated with a foot shock (Deroche-Gamonet et al, 2004;Pelloux et al, 2007;Vanderschuren and Everitt, 2004). When compared to cocaine, rats are less motivated to work for a chocolate drink and in contrast to cocaine will not seek the chocolate drink when a tone is presented that was previously associated with a foot shock, even after being exposed to palatable diets for 2 months (de Jong et al, 2013; but see: Johnson and Kenny, 2010). Although some rats may display a tendency to display addictive-like behaviors, exposure to palatable foods high in fat and sugar, did not result increase these behaviors as observed after extended access to cocaine (de Jong et al, 2013).…”
Section: A Critical Review Of Rodent Models Of "Food Addiction"mentioning
confidence: 99%
“…When compared to cocaine, rats are less motivated to work for a chocolate drink and in contrast to cocaine will not seek the chocolate drink when a tone is presented that was previously associated with a foot shock, even after being exposed to palatable diets for 2 months (de Jong et al, 2013; but see: Johnson and Kenny, 2010). Although some rats may display a tendency to display addictive-like behaviors, exposure to palatable foods high in fat and sugar, did not result increase these behaviors as observed after extended access to cocaine (de Jong et al, 2013).…”
Section: A Critical Review Of Rodent Models Of "Food Addiction"mentioning
confidence: 99%